Penerapan Metode Ummi Dalam Upaya Peningkatan Kualitas Bacaan Al Qur’an - Insiyah, Cici’ (Communautaire: Journal of Community Service, 2022)
Reading the Qur'an is one of the noble deeds. A good recitation of the Qur'an will be worth a reward for the reader and vice versa; a wrong reading will get a sin. Before reading the Koran, we must study Maharaj and tajwid properly and correctly because then we will be able to read the Koran fluently, sufficiently, and accurately. The approach method used in this activity is by using the ummi method, which is carried out to improve the reading of the Qur'an for children and adolescents in Astapah village. This activity was carried out because the ummi method became an effective learning system. After all, it could listen directly and check to understand and correct the pronunciation of the hijaiyah letters for children and adolescents in Astapah village. With this guidance, the students can also be closer to the community. Based on the results of community empowerment activities, it can be concluded that there is an increase in the knowledge and understanding of children and adolescents about makhorijul letters and tajwid after mentoring and training on how to recite the hijaiyah letters and the science of recitation so that students can read the Qur'an properly and correctly, and help the institutions where the Qur'an learns to improve the quality of reading the Qur'an for children and adolescents in Astapah village.